Advances in the Practice of Public Investment Management Portfolio Modelling, Performance Attribution and Governance (Springer International Publishing, 2018)
This book covers the latest advances in the theory and practice of public investment management. It includes the most up-to-date developments in the implementation of public asset management - including multiple contributions on portfolio allocation in varying interest-rate and credit-risk environments. Other highlights include implementation, performance attribution and governance issues surrounding reserves management, portfolio construction techniques appropriate for public investors and an in-depth discussion of the challenges to achieving international diversification.